Effects of the incorporation of honey from Apis mellifera from the Amazon savanna on the technological and sensory properties of yogurt during refrigerated storage - Manoel Henrique do Rosário Silva; Maria Clarisnete de Oliveira Moura; Esther Morais da Silva Assuncão; Kathielle Delfraxe Santos Oliveira; Mateus Lima Ramos; Adria Kemilly Costa Moura; Ana Paula Folmer Correa; Laura Adriane de Moraes Pinto; Daniela Cavalcante dos Santos Campos; Gardenia Holanda Cabral; Marcos Jose Salgado Vital; Jéssica de Oliveira Monteschio (PLoS ONE, 2026)
The development of new yogurt formulations that provide additional health benefits has gained prominence in recent years. The objective of this study was to characterize the physicochemical, antioxidant, technological, microstructural and sensory properties of the honey of Apis mellifera bees from the Amazon savanna and evaluate its inclusion at different concentrations (8%, 12%, 16% and 20%) of yogurt during 28 days of refrigerated storage. The results showed that honey is within the recommended quality parameters for this product. The amount of added honey had positive effects on the color characteristics, water holding capacity and total solids content (P < 0.05), increasing the nutritional value of the yogurt. The highest concentrations of honey (16% and 20%) presented relatively high antioxidant activity (measured via the DPPH method) and were the most sensorially accepted (P < 0.05) by consumers. In addition, the highest concentration of honey (20%) favored the stability of syneresis and resulted in higher levels of total polyphenol compounds (P < 0.05). In conclusion, the addition of honey from Apis mellifera from the Amazon savanna to yogurt formulation proved to be an effective strategy to improve the quality and acceptability of the final product. In addition to standing out as a promising ingredient for the development of functional foods, its incorporation represents a relevant innovation for the local food sector, with new perspectives for the creation of differentiated products aligned with the contemporary demands for healthy and sustainable foods.